Ultrasonic Nondestructive Testing of Li-ion Batteries for Anomaly Detection and Quality Control: Applications and Signal Processing - Mohammadreza Kari (e-Journal of Nondestructive Testing)
Use of ultrasonic nondestructive methods for quality control and testing of different types of Lithium-ion battery is progressing in recent years. This study provides a comprehensive review of the current applications and technical challenges of ultrasonic testing in inspection of lithium-ion batteries. First, basic principles and theoretical modeling of such batteries are shown. Secondly, it summarizes the most common defect types in these batteries. Finally, it talks about signal processing methods used for feature extraction and development.